The Influence of Travel Time and Transportation Costs on the Use of Online Motorbike Taxi in Palembang City - Rozandi, Ardin; Amar, Tsulis Iqbal Khairul; Permadi, Dio Damas (ASTONJADRO, 2024)
One of the cities in Indonesia that usually uses motorbike taxis or online motorbike taxi services for transportation is Palembang. Mode selection is the main stage in transportation planning and policy. Urban areas need to provide space for mobility modes and transportation infrastructure because the choice of mode affects how efficiently people can move around. The choice of transport mode is determined by competition between transport modes, which takes into account travel demand and can benefit both private and public transport. Data-based online motorcycle taxi applications facilitate consumer access by making it easier for the general public and students to confirm the driver’s identity. Online transportation is becoming increasingly common in big cities like Palembang as the transportation sector develops to better serve people’s demand for efficient mobility. This research aims to analyze how travel time and transportation costs can influence the use of online motorcycle taxi transportation in Palembang City. This research uses quantitative descriptive research, this research uses non-probability samples with a purposive approach, namely a technique for determining samples with certain opinions, so the number of samples in this research is 96 people in the city of Palembang who use online motorbike taxi transportation. Data collection techniques using questionnaires, and data analysis using multiple linear regression. Based on the research results, travel time has a significant influence on the use of online motorcycle taxis in Palembang City (0.003 < 0.05), and transportation costs have a significant influence on the use of online motorcycle taxis in Palembang City (0.000 < 0.05). Travel time and transportation costs have a significant influence on the use of online motorcycle taxis in Palembang City (0.000 < 0.05), with a model capability of 70.5%, while the remaining 29.5% of online motorcycle taxi use in Palembang City is influenced by factors others not examined in this study.